Analisis Validasi Auditor terhadap Efektivitas Pengendalian Internal Piutang: Studi Kasus Pengelolaan Piutang Lancar pada Perusahaan Manufaktur - Josephine Gunawan; Mohammad Iqbal Firdaus (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2026)
This study aims to analyze the independent auditor's validation of the effectiveness of internal controls on accounts receivable in manufacturing companies that do not establish an allowance for doubtful accounts. This phenomenon is an anomaly to the principle of accounting conservatism, which requires estimating future losses. Through a descriptive qualitative approach with in-depth interviews with three senior auditors, this study reveals that the absence of an allowance for doubtful accounts is professionally acceptable if the auditor is able to verify the quality of the receivables through strong physical evidence. The findings indicate that failures in formal documentation in large-scale manufacturing companies are often compensated by increasing control risk (R Factor) and expanding the sample size in substantive testing. Subsequent receipt procedures and collateral verification are key instruments that provide sufficient assurance for auditors to agree with the assertion of the existence and valuation of receivables. The study concludes that although upstream preventive controls are very effective in maintaining liquidity, auditors still require governance improvements through Management Letters to ensure compliance with forward-looking reporting standards.